Health technology assessment in obstetrics: advantage of tailored conservative strategy vs surgical therapies of monochorionic twin complicated by TRAP-sequence - V. I. Tsibizova; I. E. Govorov; I. I. Averkin; N. M. Khamani; D. V. Blinov (Фармакоэкономика)
Introduction. Twin reversed arterial perfusion (TRAP) syndrome is one of the types of complications of monochorial twins (MT) with a frequency of occurrence of 1:35000 births. It is characterized by the presence of the main vessel instead of a normal 4 chambers heart and intrauterine developmental abnormalities. This pregnancy requires monitoring using dynamic ultrasound diagnostics every 7 days, in accordance with current recommendations. The treatment is intrauterine laser coagulation of blood vessels of the “acardial fetus” (AP) in order to prevent the development of a threatening condition for the “fetal pump” (PP). Aim: to demonstrate the possibilities of comprehensive conservative management of monochorial pregnancy complicated by TRAP.Materials and methods. An ultrasound examinations were performed on a weekly basis in monochorionic pregnancy, complicated by TRAP within the period 12-38 weeks. Serum concentrations of biochemical markers PAPP-A (pregnancy-associated plasma protein-A) and β-hGC (β-subunit of human chorionic gonadotropin) were studied in the first trimester to predict adverse perinatal outcomes.Results. The possibility of prolonging a pregnancy complicated by TRAP without performing intrauterine surgical intervention, during which quite serious complications can occur in this category of pregnancies, has been demonstrated. In a patient with monochorionic twins complicated by TRAP, totally 27 ultrasound examinations were performed within the period 12-38 weeks. This approach made it possible to dynamically monitor the condition of a pregnant and healthy fetus and to prolong pregnancy without surgery until the full term.Conclusions. Following the existing guidelines, without tailoring for individual risk, may lead to an unreasonable increase in surgical interventions. In turn, surgery is not only accompanied by a high risk of complications (up to 15%), but also constitute a certain financial burden on the budget, determined by the state on the level of 208,000 rubles. Performing routine ultrasound examinations according to the examination protocol for monochorionic pregnancy will contribute to avoiding the complications associated with surgery and better selection for surgery as well as reducing the government costs.